Assessment of partial resistance to rice blast disease - Mukherjee, A K; Mohapatra, N K; Nayak, P (ORYZA-An International Journal of Rice, 2018)
Assessment of resistance in any plant pathosystem involves the measurement, growth and development of the pathogen in the host under the influence of the environment. Partial resistance is generally a quantitative measure of disease progress over time and thus can be assessed quantitatively by means of (i) analysis of components of resistance, (ii) estimation of different parameters for evaluation of resistance, (iii) analysis of disease progress curves and (iv) analysis of stability of resistance. In this review, we discuss the analytical approaches on each of these four aspects, beginning with the components of resistance through the parameters to the multivariate analysis of disease progress curves involving principal component analysis, cluster analysis, factor analysis, pattern analysis and also the parametric and non-parametric stability statistics to arrive at the goal of selection of partial resistance. The merits and demerits of each method of assessment are discussed and the most effective method of assessment of partial resistance in rice blast pathosystem is suggested. The analysis of disease progress curves by multivariate analysis involving principal component analysis, cluster analysis, factor analysis, pattern analysis, AMMI analysis and estimation of stability values are recommended for determination of stable partial resistant genotypes.